Spectral energy distribution of the first galaxies: contribution from pre-main-sequence stars. (21st June 2019) - Mitani, Hiroto; Yoshida, Naoki; Omukai, Kazuyuki; Hosokawa, Takashi
ABSTRACT: One of the major goals of next-generation space-borne and ground-based telescopes is to detect and characterize the first galaxies that were in place in the first few hundred million years after the big bang. We study the spectral energy distribution (SED) of the first galaxies and discuss the prospects for detection and identification. We consider very young star-forming galaxies at z  = 15 and incorporate the contribution from pre-main-sequence (PMS) stars. Unlike in the present-day galaxies, primordial protostars are not embedded in dusty gas clouds, and hence the light from them can be visible at a wide range of wavelengths. We usemesa to follow the PMS evolution and use the BT-Settl model to calculate the SED of individual PMS stars. We show that PMS stars contribute to boost the flux in the mid-infrared, and that the galaxy SED at very early evolutionary phases is overall redder than at later phases. The infrared flux contribution is comparable to that caused by emission lines powered by massive stars. We argue that the contribution from PMS stars is important for characterizing young galaxies in the early Universe and also for target selection with future deep galaxy surveys.